Understanding Regime Shifts in Social-Ecological Systems Using Data on Direct Ecosystem Service Use - Censkowsky, Philipp; Otto, Ilona M. (Frontiers in Environmental Science, 2021)
This paper takes a new look on transition processes in social-ecological systems, identified based on household use of direct ecosystem services in a case study in KwaZulu-Natal, South Africa. We build on the assumption that high dependence on local ecosystems for basic needs satisfaction corresponds to a “green loop” type of system, with direct feedbacks between environmental degradation and human well-being. Increasing use of distant ecosystems marks a regime shift and with that, the transition to “red loops” in which feedbacks between environmental degradation and human well-being are only indirect. These systems are characterized by a fundamentally different set of sustainability problems as well as distinct human-nature connections. The analysis of a case study in KwaZulu-Natal, South Africa, shows that social-ecological systems identified as green loops in 1993, the average share of households using a characteristic bundle of direct ecosystem services drops consistently (animal production, crop production, natural building materials, freshwater, wood). Conversely, in systems identified as red loops, mixed tendencies occur which underpins non-linearities in changing human-nature relationships. We propose to apply the green to red loop transition model to other geographical contexts with regards to studying the use of local ecosystem services as integral part of transformative change in the Anthropocene.